The role of tidal residual currents in the North Aegean Sea - Ioannis G. Mamoutos; Manos Potiris; Elina Tragou; Vassilis Zervakis (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Modelling the impact of present and future maritime transport on marine pollution at an environmentally sensitive coastal ecosystem (Saronikos gulf, eastern Mediterranean) - Vassilis Kolovoyiannis; Aikaterini Anna Mazioti; Manos Potiris; Ioannis Mamoutos; Elisa Majamäki; Risto Hänninen; Evangelia Krasakopoulou; Elina Tragou; Vassilis Zervakis; Mikhail Sofiev; Erik Fridell; Jaakko Kukkonen; et al. (Marine Pollution Bulletin, 2025)

Dense Water Formation in the North–Central Aegean Sea during Winter 2021–2022 - Manos Potiris; Ioannis G. Mamoutos; Elina Tragou; Vassilis Zervakis; Dimitris Kassis; Dionysios Ballas (Journal of Marine Science and Engineering, 2024)
The evolution and drivers of dense water formation (DWF) in the North–Central Aegean Sea (NCAeg) during winter 2021–2022 are studied using observations from two Argo floats and the output of an operational data-assimilating model. Dense water with σθ>29.1 kgm−3 was produced over most of the NCAeg, except for the northeastern part covered by Black Sea water (BSW), where the maximum surface density was

Status, distribution, and threats of the last surviving fan mussel populations in Greece - ORESTIS PAPADAKIS; IOANNIS MAMOUTOS; ALEXIS RAMFOS; GAETANO CATANESE; EVANGELOS PAPADIMITRIOU; JOHN THEODOROU A.; COSTAS BATARGIAS; CHARIKLEIA PAPAIOANNOU; MARIA KAMILARI; ELINA TRAGOU; VASSILIS ZERVAKIS; STELIOS KATSANEVAKIS (Mediterranean Marine Science, 2023)
Since the first confirmed records of mass mortality events (MME) in the Aegean Sea in 2018, Pinna nobilis populations in Greek seas have been decimated. To bolster recovery efforts, this study aimed to assess the status of fan mussel populations in the Aegean and Ionian seas and investigate potential recolonization through natural recruitment. From May 2022 to May 2023, 163 independent underwater visual surveys were conducted across various locations and depths along the Greek coastline. A total of 4348 P. nobilis individuals was recorded, of which 87.3% were found dead and 12.7% were alive. The sole surviving fan mussel populations were located in the semi-enclosed gulfs of Amvrakikos in the Ionian Sea and of Kalloni in the Aegean Sea, with estimated recent mortality rates (excluding potential poaching) of 7.7% and 6.3%, respectively. To track potential new recruitment, a network of larvae collectors was deployed in multiple locations. Additionally, an ocean circulation model (OCM) was developed to predict the export and fate of larvae from the surviving populations in the Marmara Sea towards the Aegean Sea. Beyond the MME, this study identified several other threats, which significantly endanger fan mussel survival. The findings of this study underscore the urgent need to implement protection measures and restoration actions to enhance the chances of P. nobilis survival and recovery in the Greek seas.

High-Resolution Model of Clew Bay—Model Set-Up and Validation Results - Hazem Nagy; Ioannis Mamoutos; Glenn Nolan; Robert Wilkes; Tomasz Dabrowski (Journal of Marine Science and Engineering, 2023)
Clew Bay is an important aquaculture production area in Ireland. In this study, we focused on a high-resolution simulation of the Clew Bay region based on a regional ocean modeling system (ROMS). Freshwater discharges from eight rivers are included in the model and a wetting–drying scheme has been implemented. The Clew Bay model simulation was validated and calibrated with available observations (e.g., acoustic Doppler current profiler (ADCP), vertical salinity and temperature profiles, and a tide gauge) in the geographic area of the model domain. High correlations were found between the model data and observed temperature, salinity and water levels, along with small root mean square errors. This indicates that the model is able to reproduce the oceanographic phenomena in the study area. The Taylor diagram analysis showed a high correlation coefficient (R = 0.99) between the observed bottom temperature in the Inner Bay and Clew Bay model, along with a small centered root mean square error (RMSD = 0.5 °C). High correlation coefficients (R > 0.80) were found between the model and the two ADCPs for the zonal current component. There was a resemblance in structure between the model and the observed salinity profiles, indicating that freshwater was correctly implemented in the model. Moreover, the correlation coefficient between the model and the tidal sea surface height (SSH) was 0.99, with an RMSD of 0.09 m. We discovered that wind direction and speed had a significant impact on the bay’s water inflow rate. The model outputs can be used to provide scientists, fishermen, and decision-makers with hydrodynamic information on ocean conditions in the bay.

Simulating the Interconnected Eastern Mediterranean–Black Sea System on Climatic Timescales: A 30-Year Realistic Hindcast - Stamatios Petalas; Elina Tragou; Ioannis G. Mamoutos; Vassilis Zervakis (Journal of Marine Science and Engineering, 2022)
Inter-basin water exchanges can be quite important in climatic-scale numerical studies simulating the circulation and hydrographic characteristics of neighboring oceanic basins connected through narrow straits. The crucial role of the interaction between the Mediterranean and the Black Seas is often overseen in simulations, which rely mostly on parameterizations to describe the exchange, essentially decoupling the two basins. In this study, the fully interconnected Eastern Mediterranean–Black Sea system is simulated for the historical period (1985–2015) using realistic boundary conditions (lateral, atmospheric and hydrological), with a hydrodynamic fully three-dimensional ocean modeling system. The setup of such a configuration is thoroughly described and the performance of the 30-year hindcast product is validated exhaustively against observations and model results, by evaluating the representation of surface fields, circulation, three-dimensional hydrographic characteristics, volumetric water exchanges, and the spatio-temporal variability of the above. The comparison shows exceptional performance, minimal drift, and substantial improvement compared to modeling studies that do not include the interaction. Moreover, due to the free-run configuration of the simulation (i.e., absence of assimilation schemes) no additional input is required other than the respective boundary conditions, making it possible to reliably extend the same setup for scenarios where observational data are not available, such as in future projections.

The Hellenic Marine Observing, Forecasting and Technology System—An Integrated Infrastructure for Marine Research - Evi Bourma; Leonidas Perivoliotis; George Petihakis; Gerasimos Korres; Constantin Frangoulis; Dionysios Ballas; Vassilis Zervakis; Elina Tragou; Petros Katsafados; Christos Spyrou; Manos Dassenakis; Serafim Poulos; et al. (Journal of Marine Science and Engineering, 2022)
Research infrastructures have been established throughout Europe in order to create robust organizations that will facilitate and enhance research and innovation processes and will advance society with innovative products and services. The Hellenic Integrated Marine Observing, Forecasting and Technology System (component of HIMIOFoTS RI) has been implemented in the framework of the National Roadmap for Research Infrastructures to form a large-scale infrastructure for the marine environment in Greece. It links together ocean observing and forecasting systems, coastal zone monitoring and management practices, as well as ocean engineering testing facilities. The overarching framework of the system supports the coordination of five organizations with expertise in the field of marine science and technology, the central management of research activities, and the common development of services and products. It comprises facilities and resources while it provides open access to research communities (academia, industry) to support the scientific advancements and innovation in their fields. The Hellenic Marine Observing, Forecasting and Technology System was further enhanced during its implementation through significant upgrades and developments in order to extend its observing capacity and the forecasting and technological abilities, while advancing the provided services and products.

A High-Resolution Numerical Model of the North Aegean Sea Aimed at Climatological Studies - Ioannis G. Mamoutos; Emmanuel Potiris; Elina Tragou; Vassilis Zervakis; Stamatios Petalas (Journal of Marine Science and Engineering, 2021)
A new, high-resolution model for the northern part of the Aegean Sea, aimed primarily at climatological research (relaxation and data assimilation-free climate simulations), is hereby presented, along with the results of a 28-year-long simulation covering the period from 1986 to 2013. The model applied is the Regional Ocean Modelling System (ROMS). A significant improvement over previous models of the Aegean introduced in this work is the replacement of parameterizations of the Dardanelles exchange by a fully three-dimensional simulation of the flow in the Strait. The incorporation of part of the Marmara Sea in the model domain enables the interaction with other regional climate simulations, thus allowing climatic variability of the exchange of the Mediterranean and Black Seas. An extensive validation is carried out comparing the model output with all the available observations from several different platforms, i.e., satellite sea surface temperature and height, T/S profiles from R/V ships, and HF radar surface currents velocity. We focus on the model’s ability to reproduce, to some extent, the distinct thermohaline features and circulation patterns that characterize this specific area of the Mediterranean Sea. Our findings, after comparing simulation results with all the available observations, revealed the model’s sufficiency to simulate very adequately the complex hydrology of the North Aegean Sea, and the model’s ability to reproduce incidents of deep-water formation that took place in the region in previous decades during the Eastern Mediterranean Transient (EMT).

Investigation of the Inherent Variability of the Mediterranean Sea Under Contrasting Extreme Climatic Conditions - Angeliki Sampatakaki; Vassilis Zervakis; Ioannis Mamoutos; Elina Tragou; Alexandra Gogou; Maria Triantaphyllou; Nikolaos Skliris (Frontiers in Marine Science, 2021)
The internal variability of the thermohaline circulation of the Mediterranean Sea is examined under contrasting extreme thermal and mass atmospheric forcing conditions. Three millennium-long numerical simulation experiments were performed under: (a) the current climatology, (b) a strong buoyancy forcing (SBF) scenario due to cold and dry conditions resembling the Younger Dryas event, and (c) a weak buoyancy forcing (WBF) scenario due to S1a sapropel deposition-like conditions (warm and wet). To isolate the inherent variability of the system, independent of interannual atmospheric forcing variability, the latter was defined as a perpetual year pertinent to each experiment. Self-diagnosed heat and salt fluxes, consistent to sea-surface characteristics of the above periods, forced three millenium-long, relaxation-free numerical experiments. These simulations were preceded by initial spin-up periods. The inherent spatiotemporal variability of the Mediterranean Sea was analyzed using the empirical orthogonal function (EOF) and spectral analysis on the simulated density fields. Our results revealed that the Mediterranean Sea exhibits high sensitivity to climatic conditions, allowing its circulation to change from anti-estuarine (for the SBF scenario, leading to a buoyancy loss to the atmosphere) to estuarine (for the WBF scenario, corresponding to a buoyancy gain from the atmosphere). In all three experiments, the interannual and decennial variabilities dominate in upper layers, and the decennial variability dominates in the Gibraltar and Sicily Straits. Under current climatic conditions the first two EOF modes express only 60% of the density variability in the deep layers. This contribution exceeds 90% under more extreme conditions. Moreover, the first EOF modes correspond to a basin-wide in-phase variability of the deep layers under the reference and WBF conditions. During SBF conditions the first modes reveal a vertical buoyancy exchange between upper and deeper layers. The second EOF mode of deep waters under both extreme scenarios showed that the western and eastern basins exchange buoyancy in decennial (for the cold/dry) and interdecennial (for the warm/humid) timescales. The residence time of the Eastern Mediterranean deep water was diagnosed to be centennial, semicentennial, and intercentennial for the cases of current period, SBF, and WBF, respectively.

Developing a Pilot Operational Oceanography System for an Enclosed Basin - Stamatios Petalas; Ioannis Mamoutos; Agisilaos-Alexandros Dimitrakopoulos; Angeliki Sampatakaki; Vassilis Zervakis (Journal of Marine Science and Engineering, 2020)
The first stages of the development of a pilot oceanographic observatory for an enclosed basin (Kalloni Gulf, Lesvos, Greece) are described. The focus of the present work is related to the estimation of the water exchange with the open sea, using a numerical model of the region, volume flux measurements based on current velocity, and sea-level measurements. Three different methods of assessment of the exchange are described and evaluated, in order to select a reference method to calibrate submarine telephone cable measurements. The high-resolution coastal circulation model for the enclosed sea, nested in a larger-domain model, is developed and evaluated against in situ data, focusing on the adequate representation of the exchange and the hydrographic structure in the basin. Monitoring the water level is selected as the best-suited method for estimating the water exchange in hourly-to-weekly time scales. The model reproduces adequately the tidal exchange and sea-level response, as well as the hydrographic characteristics of the basin. The cable voltage measurements exhibit tidal signals overwhelmed by low-frequency noise, possibly attributable to circuitry and ground failures; however, the most suitable method for estimating exchanges of the basin with the open sea appears to be sea-level monitoring.